2018
DOI: 10.1002/anie.201711535
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Aurofusarin: Studies on the Atropisomeric Stability of Bis‐Naphthoquinones

Abstract: An efficient annulation involving pyrone addition to a quinone and Dieckmann condensation was developed for rapid assembly of a γ-naphthopyrone monomeric precursor to the bis-naphthoquinone natural product aurofusarin. Dimerization was achieved through Pd -catalyzed dehydrogenative coupling. Further studies employing asymmetric nucleophilic epoxidation indicate that the atropisomers of aurofusarin and derivatives are not configurationally stable at ambient temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…In addition, no interconversion of 1 and 16 was observed after thermolysis of either compound in refluxing toluene for 24 h. The rotational barrier for interconversion of atropisomers was calculated to be 47.5 kcal/mol using the B3LYP/6-31G(d) level of theory. 5 Although the rotational barrier is high, the Pappo group 11a and others 39 have demonstrated that BINOL can undergo racemization under oxidative conditions. This prompted us to examine single electron transfer (SET) conditions with either atrop -gonytolide A ( 16 ) or its brominated precursor bromo- atrop -gonytolide A ( 27 ) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, no interconversion of 1 and 16 was observed after thermolysis of either compound in refluxing toluene for 24 h. The rotational barrier for interconversion of atropisomers was calculated to be 47.5 kcal/mol using the B3LYP/6-31G(d) level of theory. 5 Although the rotational barrier is high, the Pappo group 11a and others 39 have demonstrated that BINOL can undergo racemization under oxidative conditions. This prompted us to examine single electron transfer (SET) conditions with either atrop -gonytolide A ( 16 ) or its brominated precursor bromo- atrop -gonytolide A ( 27 ) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…If any one of the four involved enzymes were knocked out, no dimer formation was observed . The stereoselectivity of the coupling reaction is difficult to determine because aurofusarin does not form stable atropisomers due to its quinone moieties …”
Section: Methodsmentioning
confidence: 99%
“…The basic factors that determine the observed stereoselectivity were investigated. Rotation around the biaryl bond, a consequence of BINOL-to-metal charge transfer, results in a rapid loss of optical purity in 3,3′-unsubstituted BINOLs. ,,, Similarly, ( R a )-NOBIN- 2 underwent complete racemization within 5 h in the presence of FeCl 3 (10 mol %, Figure A, black circles); this phenomenon was utilized by Kočovsky for the kinetic resolution of 2 by a stoichiometric amount of chiral copper amine complexes . Furthermore, a rapid atropoisomerization process took place when NOBINs 6a and 7a were treated in two separate vials under the reaction conditions, leading to the formation of thermodynamic mixtures with similar diatereoisomeric ratios ( 6a : 7a , 1.5:1, Figure B, red and blue circles).…”
mentioning
confidence: 99%